Perioperative Opioid-Related Harms: Opportunities to Minimize Risk - Alessio-Bilowus, Dominic; Luby, Alexandra O.; Cooley, Samantha; Evilsizer, Sarah; Seese, Elizabeth; Bicket, Mark; Waljee, Jennifer F. (Seminars in Plastic Surgery, 2024)
Although substantial attention has been given to opioid prescribing in the United States, opioid-related mortality continues to climb due to the rising incidence and prevalence of opioid use disorder. Perioperative care has an important role in the consideration of opioid prescribing and the care of individuals at risk for poor postoperative pain- and opioid-related outcomes. Opioids are effective for acute pain management and commonly prescribed for postoperative pain. However, failure to align prescribing with patient need can result in overprescribing and exacerbate the flow of unused opioids into communities. Conversely, underprescribing can result in the undertreatment of pain, complicating recovery and impairing well-being after surgery. Optimizing pain management can be particularly challenging for individuals who are previously exposed to opioids or have critical risk factors, including opioid use disorder. In this review, we will explore the role of perioperative care in the broader context of the opioid epidemic in the United States, and provide considerations for a multidisciplinary, comprehensive approach to perioperative pain management and optimal opioid stewardship.
Keywords: perioperative opioid prescribing; new persistent opioid use; opioid use disorder; care coordination